POLYCYSTIC OVARY SYNDROME: RISK FACTORS AND ASSOCIATED FEATURES AMONG UNIVERSITY STUDENTS IN PAKISTAN - Tariq Feroz Memon1, Mehwish Channar2, Syed Abdul Wadood Shah3, Aiman Shaikh4, MehwishBatool5 , NomaShri6. , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2020)
Objective: To evaluate the risk factors and common clinical features existent among the female students with polycystic ovary syndrome at ISRA University, Hyderabad, Pakistan. Methods: Cross-sectional study was carried out at the ISRA University Hyderabad, Sindh, Pakistan between February 2019 and July 2019. The female students from the medical section were selected using a simple random sampling technique. All-female students between 19 to 24 years studying in (1st to 5th-year MBBS) were included. While those students studying in other departments (other than MBBS) were excluded. Ethical approval was sought from the ethical review committee of the university. Rotterdam’s criterion was used for the confirmation of the diagnosis of the syndrome. SPSS version 22 was used for the statistical analysis of the data. The level of p-values <0.05 was considered to be statistically significant. Results: Around 40% of participants reported to have menstrual disturbances. The majority (31.7%) of them had been dealing with the syndrome for more than three years. PCOS was prevalent among 37.3% of study participants. PCOS was more prevalent (59.4%) among participants in their late adolescence (22-24 years). A statistically significant difference (p-value <0.05) in mean age of menarche, BMI, Hirsutism score and WHR between participants diagnosed having PCOS in comparison with those without PCOS. Conclusion: The prevalence of PCOS is high among adolescent female. Genetic predisposition is the main risk factor (positive family history of PCOS while menstrual disturbances are the most frequent clinical feature.